The Effect of Ecological and Geographical Factors on Environmental Parameters as a Background for Vegetables Selection (Agricultural Engineering, 2018)
The aim of the study is to find out the role of the ecological and geographical fator in obtaining sustainable yields and the assessment of the environment as a background for the selection in breeding of vegetable adaptive ability. Objects of research: winter garlic, vegetables beans, headed salad. Research was conducted in various ecological and geographical zones of Belarus, Russia, Uzbekistan. Environmental parameters as the background for selection were determined using Kilchevsky’s, L. V. Hotyleva’s (1985), technique, Kilchevsky (1985). Differences between testing points on environmental parameters for determining the trait “yielding capacity” have been revealed, maximum environmental productivity at assessing various genotype sets has been determined. Long-term research showed that sustainable productivity depends on the ability of a genotype to respond to environmental conditions. Based on the obtained results, statistical parameters of quantity traits of the parent material, their variability depending on ecological-geographical factor and the character of influence on the potential yields and ecological sustainability have been received. Using various ecological and geographical zones helps to reveal the potential of plants in given conditions on sustainability and productivity parameters. Testing of winter garlic, beans, head salad allowed differentiation of them according to adaptability capacity at various set of genotypes. It was found out that research must be carried out at highly productive and analyzing backgrounds to get the required material. One of the main methods enabling to increase plant selection efficiency is the use of natural ecological backgrounds.